Bone grafts in periodontal therapy - Sukumar, Sujith; Drízhal, Ivo (Acta medica (Hradec Kralove), 2008)
This article is limited to a review of bone replacement graft materials used in periodontal therapy. The source, mode of bone regeneration and the respective advantages and disadvantages of autogenous, allogenic, xenogenic and alloplastic materials are discussed.
Keywords: transplantace kostí; Periodontal Diseases; Bone Substitutes; nemoci parodontu; kostní náhrady; Humans; lidé; Bone Transplantation